1998
DOI: 10.3109/03005364000000091
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Screening Outcomes from Click-Evoked Otoacoustic Emissions and Auditory Brainstem Response Tests

Abstract: Transiently evoked otoacoustic emissions (TEOAE) and auditory brainstem response (ABR) tests were used in parallel to screen 862 neonates with risk factors for hearing loss. Seven neonates (0.81%) passed on TEOAE screen yet failed on ABR in one ear (six neonates) or both ears (one neonate). This combination of results has been termed 'anomalous'. Examination of audiometric results obtained on follow-up shows that in one ear of one neonate the result was consistent with the later confirmed audiogram shape. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Deltenre et al [1997] reported cases of desynchronized ABRs, intact cochlear microphonics and click evoked OAEs in infants with hyperbilirubinemia needing exchange transfusion. According to Wood et al [1998], this pattern of results accounted for 0.81% (7/862) of those failing at least 1 ear. Interestingly, this percentage is similar to the 2.0% of healthy newborn infants that have bilirubin levels exceeding 20 mg/dl [Newman et al, 1999].…”
Section: Electrophysiological Evidence Of Auditory System Involvementmentioning
confidence: 99%
“…Deltenre et al [1997] reported cases of desynchronized ABRs, intact cochlear microphonics and click evoked OAEs in infants with hyperbilirubinemia needing exchange transfusion. According to Wood et al [1998], this pattern of results accounted for 0.81% (7/862) of those failing at least 1 ear. Interestingly, this percentage is similar to the 2.0% of healthy newborn infants that have bilirubin levels exceeding 20 mg/dl [Newman et al, 1999].…”
Section: Electrophysiological Evidence Of Auditory System Involvementmentioning
confidence: 99%